2008
DOI: 10.1007/s11060-008-9556-y
|View full text |Cite
|
Sign up to set email alerts
|

XRCC1 and XRCC3 variants and risk of glioma and meningioma

Abstract: Several single nucleotide polymorphisms (SNPs) affecting DNA repair capacity and modifying cancer susceptibility have been described. We evaluated the association of SNPs Arg194Trp, Arg280His, and Arg399Gln in the X-ray cross-complementing group 1 (XRCC1) and Thr241Met in the X-ray cross-complementing group 3 (XRCC3) DNA repair genes with the risk of brain tumors. The Caucasian study population consisted of 701 glioma (including 320 glioblastoma) cases, 524 meningioma cases, and 1,560 controls in a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 23 publications
7
67
0
3
Order By: Relevance
“…Among them, the XRCC1 Arg194Trp variant located in the proliferating cell nuclear antigen (PCNA) binding region, which suggests that this mutation may be result in gliomagenesis. However, these studies have failed to yield a consistent conclusion (Kiuru et al, 2008;Liu et al, 2009;McKean-Cowdin et al, 2009;Rajaraman et al, 2010;Custodio et al, 2011;Hu et al, 2011;Zhou et al, 2011;Liu et al, 2012;Luo et al, 2013;Pan et al, 2013;Wang et al, 2012;Xu et al, 2013).…”
Section: Research Articlementioning
confidence: 99%
See 2 more Smart Citations
“…Among them, the XRCC1 Arg194Trp variant located in the proliferating cell nuclear antigen (PCNA) binding region, which suggests that this mutation may be result in gliomagenesis. However, these studies have failed to yield a consistent conclusion (Kiuru et al, 2008;Liu et al, 2009;McKean-Cowdin et al, 2009;Rajaraman et al, 2010;Custodio et al, 2011;Hu et al, 2011;Zhou et al, 2011;Liu et al, 2012;Luo et al, 2013;Pan et al, 2013;Wang et al, 2012;Xu et al, 2013).…”
Section: Research Articlementioning
confidence: 99%
“…One study conducted in region of Europe with 700 glioma patients and 1556 controls reported that no association between the Arg194Trp polymorphism and glioma cancer risk (Kiuru et al, 2008). The other studies in USA consisted of a total sample size (1514 cases and 2755 controls) showed that Arg194Trp did not confer an effect on glioma (Liu et al, 2009;McKean-Cowdin et al, 2009;Rajaraman et al, 2010).…”
Section: Confirmed Of Biomarkers Of Genetic Factors Could Expectmentioning
confidence: 99%
See 1 more Smart Citation
“…We have listed about 20 epidemiological studies reporting positive associations between DNA repair polymorphisms and cancer risk (Table 1 [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] ). Only a small proportion of studies were large (five studies were more than 500 pair cases and controls) and population based; however, some consistencies in results are apparent.…”
Section: Pbts Molecular Epidemiologic Studies With Focus On Dna Repairmentioning
confidence: 99%
“…Currently, the etiology of glioma has not been completely understood. Previous studies have reported that a number of single nucleotide polymorphisms (SNPs) in DNA repair gene may modify glioma risk (Wang et al, 2004;Wrensch et al, 2005;Kiuru et al, 2008;Liu et al, 2009;Zhou et al, 2009;Rajaraman et al, 2010;Hu et al, 2011;Yosunkaya et al, 2010;Zhou et al, 2011). However, the clinical value of most glioma-associated molecular aberrations in terms of their significance as diagnostic, prognostic or predictive molecular markers has remained unclear (Batchelor et al, 2004;Ohgaki et al, 2004;Houillier et al, 2006).…”
Section: Introductionmentioning
confidence: 99%